Cyclic load tests and seismic performance of recycled aggregate concrete (RAC) columns. (20th January 2019) - Liu, Chao; Fan, Jincheng; Bai, Guoliang; Quan, Zonggang; Fu, Guangming; Zhu, Chao; Fan, Ziyu
Highlights: The seismic performance of recycled aggregate concrete columns (RAC) was investigated. The failure process of RAC columns and natural aggregate concrete column is similar. The effect of parameters on the seismic performance of columns is discussed. The shear deformation of the plastic hinge region of the column was discussed. Abstract: In this paper, four one-two-scale recycled aggregate concrete (RAC) columns were prepared and tested under reversed quasi-static cyclic loading. Three levels of recycled coarse aggregate (RCA) replacement ratios (0%, 50% and 100%) and two axial load ratios (0.15 and 0.35) were considered to investigate and analyze the seismic performance of RAC columns. The test results indicate that the failure process of RAC columns is similar to that of natural aggregate concrete (NAC) columns and presented satisfactory seismic requirements in terms of hysteresis behavior, ductility and energy dissipation capacity. The results also show that the RCA replacement ratios effect on seismic is significant, and the axial load ratio had an obvious influence on the energy dissipation capacity and shear deformation of the columns. Therefore, the axial load ratio must be controlled strictly in seismic design.